Norway : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper describes wages and competitiveness in Norway. Norway may have to downwardly revise its expectations for wage growth if it is to avoid a significant loss of competitiveness and manage the transition to a less oil-dependent economy. Norway was able to afford very high wage growth in the past (notwithstanding the noted challenges in several sectors) thanks to good fortune in its terms of trade. Going forward, it would be prudent not to count on being fortunate twice: wage moderation would help build resilience in case of less favorable trends in international prices. It would also help facilitate the needed transition out of oil by supporting sectors that did not benefit from past terms of trade gains. Communication from the government can continue to help in managing public expectations. Fiscal policy plays a key role in promoting competitiveness and containing the spending effect of Dutch Disease. After a prolonged expansion of fiscal policy-partly enabled by large valuation gains of the sovereign wealth fund-it is now appropriate to gradually start tightening fiscal policy. The ongoing up-cycle provides an ideal setting to get started on structural consolidation, which will ultimately be needed to face to address aging pressures.